Protein Abundance of Clinically Relevant Multidrug Transporters along the Entire Length of the Human Intestine - Drozdzik, Marek; Gröer, Christian; Penski, Jette; Lapczuk, Joanna; Ostrowski, Marek; Lai, Yurong; Prasad, Bhagwat; Unadkat, Jashvant D; Siegmund, Werner; Oswald, Stefan (Molecular pharmaceutics, 2014)
Intestinal transporters are crucial determinants in the oral absorption of many drugs. We therefore studied the mRNA expression (N = 33) and absolute protein content (N = 10) of clinically relevant transporters in healthy epithelium of the duodenum, the proximal and distal jejunum and ileum, and the ascending, transversal, descending, and sigmoidal colon of six organ donors (24–54 years). In the small intestine, the abundance of nearly all studied proteins ranged between 0.2 and 1.6 pmol/mg with the exception of those of OCT3 (<0.1 pmol/mg) and PEPT1 (2.6–4.9 pmol/mg) that accounted for ∼50% of all measured transporters. OATP1A2 was not detected in any intestinal segment. ABCB1, ABCG2, PEPT1, and ASBT were significantly more abundant in jejunum and ileum than in colon. In contrast to this, the level of expression of ABCC2, ABCC3, and OCT3 was found to be highest in colon. Site-dependent differences in the levels of gene and protein expression were observed for ABCB1 and ASBT. Significant correlations between mRNA and protein levels have been found for ABCG2, ASBT, OCT3, and PEPT1 in the small intestine. Our data provide further physiological pieces of the puzzle required to predict intestinal drug absorption in humans.